The Staging of Examinations: A Student Response to the Institutional Perspective - Albas, Daniel; Albas, Cheryl (Canadian Journal of Higher Education, 1988)
When universities administer examinations, they do so dramaturgically. That is, they use spaces, props, equipment, and bodies to convey specific messages (that examinations are important, serious, formal affairs which reflect the larger societal values of universalism and individualism) to students. Drama and dramaturgy require both actors and an audience; the interaction consists of the effect that the one has on the other, that the other has on the one and both of these. The focus of this paper is on the interaction between the message and students’ response to it, that is, the students’ definition of the situation. In particular, emphasis is upon the notion that the dramaturgical messages given by the university will be interpreted largely as they were intended to be, that in some cases the effect of the message is dysfunctional, either because it is misinterpreted or because it is challenged.